The Razuhuillca micro-watershed in dispute: hydromorphological dynamics and territorial resistance to mining concessions in the Peruvian Andes - Cárdenas Morales, Bruno Kadafi; Mendoza Colos, Manuel; Herrera Díaz, Santos Clemente; Carhuallanqui Ibarra, Solón Dante; Castro Aponte, Walter Victor; Gómez Ccochachi, Yirme Yohu; Huari Salazar, Yodel Cheldo; Oré Gálvez, Saríah Fanny; Lozano Rodríguez, Jorge Luis; Huayhua Lévano, Fernando Gari; Paytan Montañez, Tulio Celestino; Barnes, Crispin H. W.; et al. (Frontiers in Water, 2025)
The Razuhuillca micro-watershed, located in the Andean province of Huanta (Peru), illustrates the convergence of hydro-territorial fragility and socio-environmental conflict. Through a mixed-methods approach— combining quantitative morphometric analysis using GIS and DEMs with qualitative semi-structured interviews coded in Atlas.ti—this study reveals how strategic headwater zones for water recharge overlap with both legal and illegal mining activities. These extractive pressures compromise hydrological regulation and generate spatial, cultural, and political tensions. Local communities perceive water as a sacred and relational element, and invoke Apu Razuhuillca as a territorial guardian beyond state legality. Narratives of affective territoriality, institutional distrust, and autonomous resistance—such as community patrols and demands for protection—highlight the emergence of bottom-up governance in response to extractive threats. In this context, water is not merely a resource but a symbol of identity, care, and territorial legitimacy. The findings underscore the need for a sociohydrological approach that integrates ecological indicators, spatial risk, and lived experiences. The Razuhuillca micro-watershed stands as a threatened yet defended socio-ecosystem, where technical, cultural, and political dimensions of water governance intersect.